Legal Protection for Consumers Using Online Motorcycle Taxi Services in the Red Zone Area of Motorcycle Taxi Bases Linked to Law No. 8 of 19999 Concerning Consumer Protection - Diki Rexsi; Yuniar Rahmatiar; Muhamad Abas (Dinasti Research, 2026)
This study examines legal protection for consumers using online motorcycle taxi services in areas commonly referred to as red zones of conventional motorcycle taxi bases. The issue arises due to operational restrictions imposed on online motorcycle taxi drivers in certain areas, which limit consumers’ ability to freely choose transportation services. The purpose of this research is to analyze the forms of legal protection for consumers and the responsibilities of service providers and the government in ensuring consumers’ freedom to choose transportation services. This research uses a normative legal research method with statutory and conceptual approaches through the analysis of legislation, legal literature, and legal doctrines related to consumer protection and transportation services. The results indicate that legal protection for consumers of online motorcycle taxi services is guaranteed through consumer protection regulations that recognize the rights of consumers to safety, comfort, and freedom to choose services. In addition, the responsibility of service providers and the government is essential in ensuring a fair transportation system that provides legal certainty for society. Therefore, cooperation between service providers and the government is necessary to ensure optimal protection of consumer rights.